Traditional neurotherapeutics approach intended for direct nose to brain delivery. (14th September 2017) - Abolhasanzadeh, Zohreh; Ashrafi, Hajar; Badr, Parmis; Azadi, Amir
Abstract: Ethnopharmacological relevance: Nasal delivery systems have a significant role in Persian traditional medicine. Most of them were utilized for central nervous system (CNS)-related disorders. In modern medicine, nasal drug delivery systems for brain delivery are highly regarded. Aim of the study: Despite recent advances in drug delivery to the (CNS), delivery of therapeutics to the brain remains a major challenge because of the blood brain barrier (BBB). There are several mechanisms which regulate the drug transfer across the BBB. Local administration methods of therapeutic agents are often associated with adverse events, while the intranasal pathway has been suggested as a non-invasive alternative route to deliver drugs to the brain. This route can bypass the BBB and deliver drug molecules directly to the CNS. There are different nasal formulations have been addressed in Persian traditional pharmacopeias. The present review attempt to explore the famous and practical Qarabadin to find ancient nasal dosage forms. Materials and methods: With an explore on traditional herbs in google scholar, scopus and science direct, we have found some original and review articles which have demonstrated our findings on the use of traditional herbs for CNS disorders. Four encyclopedia of multi-component formulations, including Qarabadin Salehi (1766), Qarabadin kabir (1781), Qarabadin Ghaderi (18th century), and Qarabadin Azam (1853), were searched for nasal formulations having CNS-related indications. Formulations were categorized based on dosage forms, and also, diseases which they were suggested for. While the names of illnesses were in ancient terminology of Traditional Medicine, they were translated to modern medical terminology by comparing their definitions, signs, and symptoms from two medical systems. Typical samples of each dosage form have been mentioned with details like amount of ingredients, scientific names of plants, and considerations pertaining to preparation or usage. Results: Among all traditional nasal formulations, seven types were found that is used for sicknesses relating to CNS including Saoot, Nafookh, Atoos, Nashoogh, Shamoom, Lakhlakheh, and Bakhoor . Conclusions: The findings of this study reveal the physicochemical characteristics of each formulation, route of administration, and type of disease which they are suitable and also present some famous formulations. Graphical abstract: